Epidural dexamethasone-21-palmitate for spinal stenosis-related pain: a retrospective cohort study using patient-reported outcome data - Anja Lehmann; Matthijs de Leeuw; Wilhelm Ruppen; Tobias Schneider (Swiss Medical Weekly)
OBJECTIVE: Epidural steroid infiltration has been used for decades as symptomatic pain therapy. To record and evaluate treatment response to epidural steroid infiltration, patient-reported outcome data were collected from patients receiving interlaminar or transforaminal epidural steroid infiltration with dexamethasone-21-palmitate (Lipotalon®).